2010
DOI: 10.1590/s1413-70542010000200003
|View full text |Cite
|
Sign up to set email alerts
|

Carboidratos e matéria seca de tubérculos de cultivares de batata influenciados por doses de nitrogênio

Abstract: RESUMONeste trabalho, objetivou-se avaliar o efeito de doses de nitrogênio (N) sobre os teores de carboidratos (açúcares solúveis totais, açúcares redutores e amido), matéria seca e sólidos solúveis totais nos tubérculos de quatro cultivares de batata. Os tubérculos originaram-se de quatro experimentos, realizados simultaneamente no campo, no outono/inverno, na Universidade Federal de Viçosa. Em todos os experimentos, foi utilizado delineamento em blocos casualizados, com quatro repetições. Os tratamentos fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
1
14
0
10
Order By: Relevance
“…4f). Braun et al (2010), comparing the physico-chemical characteristics of potato cultivars Asterix and Atlantic cultivar with Ágata, found that the potato cultivar Ágata showed higher reducing sugars in relation with the others (9.34 g reducing sugar per 100 g of dry matter). Ezekiel et al (2007) studied the effects of gamma radiation on three cultivars of potato and verifi ed that there was further degradation of starch with the POTATO (Solanum tuberosum L.) AFTER IRRADIATION 949 highest dose of 0.50 kGy, which generated a higher concentration of sugars.…”
Section: Starch and Sugar Reduction (%)mentioning
confidence: 99%
“…4f). Braun et al (2010), comparing the physico-chemical characteristics of potato cultivars Asterix and Atlantic cultivar with Ágata, found that the potato cultivar Ágata showed higher reducing sugars in relation with the others (9.34 g reducing sugar per 100 g of dry matter). Ezekiel et al (2007) studied the effects of gamma radiation on three cultivars of potato and verifi ed that there was further degradation of starch with the POTATO (Solanum tuberosum L.) AFTER IRRADIATION 949 highest dose of 0.50 kGy, which generated a higher concentration of sugars.…”
Section: Starch and Sugar Reduction (%)mentioning
confidence: 99%
“…As stated in Braun et al (2010), starch corresponds from 60 to 80% of dry matter and sugars: glucose, fructose, and sucrose are the major carbohydrates present in the tubers. As reported by Silveira (2008), the conversion into ethanol takes around 160 L t -1 for sweet potato clone samples with an average yield of 65.5 t ha -1 and average starch concentration of 24.4% in natural weight (NW).…”
Section: Resultsmentioning
confidence: 99%
“…A aplicação de 0 e 880 kg ha -1 de K 2 O reduziu o teor de matéria seca dos tubérculos de 18,2 para 14,1%, todavia, dentro dos valores adequados para a cultivar 'Ágata' (Braun et al, 2010). Com a dose de 392,5 ha (Haase et al, 2007), com maior efeito quando o K foi aplicado na forma de cloreto de potássio do que quando aplicado na forma de sulfato de potássio (Allison et al, 2001).…”
Section: Resultsunclassified
“…Com a dose de 392,5 ha (Haase et al, 2007), com maior efeito quando o K foi aplicado na forma de cloreto de potássio do que quando aplicado na forma de sulfato de potássio (Allison et al, 2001). A percentagem de matéria seca é característica importante, indicativa da qualidade dos tubérculos pós-colheita, especialmente para a indústria de processamento (Haase et al, 2007;Braun et al, 2010).…”
Section: Resultsunclassified
See 1 more Smart Citation